Familial Dilated Cardiomyopathy Associated With a Novel Combination of Compound Heterozygous TNNC1 Variants - Landim-Vieira, Maicon; Johnston, Jamie R.; Ji, Weizhen; Mis, Emily K.; Tijerino, Joshua; Spencer-Manzon, Michele; Jeffries, Lauren; Hall, E. Kevin; Panisello-Manterola, David; Khokha, Mustafa K.; Deniz, Engin; Chase, P. Bryant; et al. (Frontiers in Physiology, 2020)
Familial dilated cardiomyopathy (DCM), clinically characterized by enlargement and dysfunction of one or both ventricles of the heart, can be caused by variants in sarcomeric genes, including TNNC1 (encoding cardiac troponin C, cTnC). Here, we report the case of two siblings with severe, early-onset DCM who were found to have compound heterozygous variants in TNNC1: p.Asp145Glu (D145E) and p.Asp132Asn (D132N), which were inherited from the parents. We began our investigation with CRISPR/Cas9 knockout of TNNC1 in Xenopus tropicalis, which resulted in a cardiac phenotype consistent with DCM. Despite multiple maneuvers, we were unable to rescue the tadpole hearts with either human cTnC wild-type or patient variants to investigate the cardiomyopathy phenotype in vivo. We therefore utilized porcine permeabilized cardiac muscle preparations (CMPs) reconstituted with either wild-type or patient variant forms of cTnC to examine effects of the patient variants on contractile function. Incorporation of 50% WT / 50% D145E into CMPs increased Ca2+ sensitivity of isometric force, consistent with prior studies. In contrast, incorporation of 50% WT / 50% D132N, which had not been previously reported, decreased Ca2+ sensitivity of isometric force. CMPs reconstituted 50-50% with both variants mirrored WT in regard to myofilament Ca2+ responsiveness. Sinusoidal stiffness (0.2% peak-to-peak) and the kinetics of tension redevelopment (kTR) at saturating Ca2+ were similar to WT for all preparations. Modeling of Ca2+-dependence of kTR support the observation from Ca2+ responsiveness of steady-state isometric force, that the effects on each mutant (50% WT / 50% mutant) were greater than the combination of the two mutants (50% D132N / 50% D145E). Further studies are needed to ascertain the mechanism(s) of these variants.